CHURCH MUSIC EDUCATION AND PRECENTOR PRACTICE IN THE REFORMED CHURCH DISTRICT OF KIRÁLYHÁGÓMELLÉK - Orosz, Otília Valéria (PUPIL: International Journal of Teaching, Education and Learning, 2021)
The Reformed Church District of Királyhágómellék was founded in 1921. After the first world war, as a result of the Trianon border change, the church leadership of the part detached from the Trans - Tisza Reformed Church District (Partium) led by István Sulyok, the bishop of Oradea, decided to create a separate diocese. The administrative county boundaries in force today do not match the boundaries of a hundred years ago, it can be attributed to the fact that the dioceses of Satu-Mare and Sălaj belonged to the Transylvanian district, so in these dioceses, the Transylvanian hymnbook and choral books edited by Samu Borsay and Gábor Veress were in use. In this period the cantor’s training took place only in Partium and Transylvanian teacher-training institutes. During communism, cantors were mostly prepared privately for the periodic cantor examination. The Oradea Cantor – Training Course in the Reformed Church District of Királyhágómellék started in 2006. In my dissertation, I discuss the cantor – training and cantor service in the Partium area, from 1921 to the present day.